Understanding the climate, migration, social protection nexus from a youth mobility dimension: Can social protection address the drivers of climigration? - Ncube, Tomy; Zualii, Lalhmangaihzuali; Murray, Una; Nguyen, Nam; Liebig, Theresa; Krendelsberger, Alexandra; Pacillo, Grazia; McKeown, Peter C.; Laderach, Peter; Spillane, Charles (Informa UK Limited, 2025)
Climate change is a threat multiplier for human migration, with those reliant on rain-fed agriculture being particularly vulnerable to climate change. This can manifest as increased poverty and potentially as climate-induced migration to seek alternative livelihood options. The interactions between climate vulnerability and social protection policy, in particular how they shape migration patterns, are poorly understood. There is significant potential for social protection programmes to positively shape migration-related decisions amongst rural youth, while enabling climate resilience. Less attention has been paid to patterns of migration within (and between) African countries, compared to migrants moving to the Global North. Here we review how social protection programmes are being (or can be) used to shape climate-induced migration decisions amongst youth in rural Africa. Based on key components of social protection (social assistance and labour market interventions), we argue that when these are adapted to meet the priorities of rural youth, a more just transition can be achieved (i.e. climate-resilient rural communities retaining rural skilled labour as opposed to climate-induced distress migration). More accurate evidence on migration drivers, and challenges faced by rural youth in accessing and benefiting from social protection, is necessary to fully inform climate migration and social protection practices.